PENGARUH PEMBERIAN BEKATUL DAN TEPUNG TEMPE TERHADAP PROFIL GULA DARAH PADA TIKUS YANG DIBERI ALLOXAN (The Influence of Rice bran and Flour Tempeh on Blood Sugar Profile in Rats Fed Alloxan) - Sufiati Bintanah; Hapsari Sulistya Kusuma (Universitas Muhammadiyah Semarang, 2010)
One of the food as an option in the menu diet is soy-based food. Study at diabetic mice treated with bran oil diet improved insulin sensitivity. Whether the effect of bran, tempeh flour, rice bran and tempeh mixture of blood sugar profiles in Wistar rats fed alloxan. Top of FormThis study aims to determine the effect of blood glucose profile after administration of bran, tempeh flour, rice bran and tempeh mixture in mice that had been given alloxan. The study was a randomized experimental laboratory using pre post test design with control group. Number of rats 6 tails for each group (3 groups of treatment and 1 control group) so that the overall sample sum was 24 rats. Results of study the Through of post hoc test showed that differences in blood sugar levels every week in all three treatment groups when compared with the control group was statistically significant (p = 0.000, p = 0.000, p = 0.000). Tempeh group as compared with mixed groups differences in blood sugar levels in 3 weeks was not significant (p = 0.491, p = 0.764, p = 0.319). Rice bran group than the group differences in levels of sugar mixture in 3 weeks was not significant (p = 0.374, p = 0.297, p = 0.093). Tempe rice bran group than the group differences in blood sugar levels at 3 weeks was not significant (p = 1.000, p = 0.993, p = 0.954). Simak Baca secara fonetik Kamus - Lihat kamus yang lebih detail Menerjemahkan lebih dari 50 bahasa παραλία Comment allez-vous ? ¿Cómo estás? sư tử กาแฟ Wie heißen Sie? nazdar! さようなら mijn vriend Простите La voiture děti escargots Je parle un petit peu français. miracoloso Buongiorno Principessa! आज मेरा जन्मदिन हैं. χρησμός haydi gidelim Wie spät ist es? Vær så snill rouge سلحفاة Ich bin vierzig Jahre alt שמח Es ist sehr interessant! Wie bitte? Langweilig hoje está ensolarado 국수 Je ne sais pas ! बन्दर hello Lakukan banyak hal dengan Google Terjemahan Jangkau pengunjung internasional. Tambahkan teks terjemahan ke video YouTube Anda. Bangun bisnis global Anda. Iklankan ke berbagai bahasa menggunakan Google Peluang Pasar Global. Tetap berhubungan dengan sahabat pena Anda di Paris. Aktifkan terjemahan otomatis untuk email dan ngobrol di Gmail. Ingin agar penggemar di Norwegia dapat membaca blog Anda? Pasang Elemen Google Terjemahan untuk menerjemahkan dengan mudah. The substitution tempeh flour, rice bran, and mix both in diabetic rats by 50% of daily food intake can lower blood sugar levels every week compared to untreated mice. Key words: soybean, rice bran, blood sugar levels, diabetic.